2022
DOI: 10.1002/celc.202200223
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Ether‐Based Electrolyte for Supercapacitors with Increased Working Voltage and Suppressed Self‐discharge

Abstract: The application of supercapacitors for long-term energy storage is largely limited by their low energy density and self-discharge behavior. Finding a way to effectively increase the voltage window (and thus the energy density) and suppress the selfdischarge of supercapacitors is a huge research challenge. Herein, by introducing a fluorinated ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), in triethyl ammonium tetrafluoroborate/acetonitrile solution as the electrolyte of supercapacitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Subsequent studies found that adding a fluorinated ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), into TEABF 4 /AN electrolyte could improve the stability of the electrolyte. As a result, a high working voltage of 3.6 V was assembled, which was much higher than the typical working voltage of 2.7 V for AN-based electrolytes without TTE [92]. In addition, the leakage current of TEABF 4 -TTE/AN was smaller than that of electrolyte without TTE at the same charging voltage, and no decomposition of electrolyte was observed at 3.6 V. When charged to 3.6 V, the open-circuit voltage of ELDC with TEABF 4 -TTE/AN decayed by 2.03 V after 24 h, which was lower than that of the EDLC without TTE (2.60 V).…”
Section: Adding Co-solvents To An or Pc For High Voltagementioning
confidence: 92%
“…Subsequent studies found that adding a fluorinated ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), into TEABF 4 /AN electrolyte could improve the stability of the electrolyte. As a result, a high working voltage of 3.6 V was assembled, which was much higher than the typical working voltage of 2.7 V for AN-based electrolytes without TTE [92]. In addition, the leakage current of TEABF 4 -TTE/AN was smaller than that of electrolyte without TTE at the same charging voltage, and no decomposition of electrolyte was observed at 3.6 V. When charged to 3.6 V, the open-circuit voltage of ELDC with TEABF 4 -TTE/AN decayed by 2.03 V after 24 h, which was lower than that of the EDLC without TTE (2.60 V).…”
Section: Adding Co-solvents To An or Pc For High Voltagementioning
confidence: 92%